Liquid – Solid mass transfer behaviour of heterogeneous reactor made of a rotating tubular packed bed of spheres. (November 2018) - Abdel-Aziz, M.H.; Nirdosh, I.; Sedahmed, G.H.
Highlights: Mass transfer behaviour of a rotating tubular packed bed of spheres was studied. Parameters studied are rotation speed, physical properties of the solution, and bed thickness. A dimensionless equation was obtained and can be used to design and scale up of the reactor. Various environmental applications of the suggested reactor were discussed. Abstract: The mass transfer behaviour of a rotating tubular packed bed of spheres was studied using an electrochemical technique which involved measuring the limiting current of the cathodic reduction of potassium ferricyanide in a large excess of supporting electrolyte. Variables studied were bed rotation speed, physical properties of the solution, and bed thickness (L). The mass transfer coefficient was found to increase with increasing bed rotation speed and decreases with increasing bed thickness. The mass transfer data were correlated by the equation: Sh = 0.126 Sc 0.33 Re 0.52 L d P - 0.8 Importance of the present study in the design and operation of high space – time yield heterogeneous reactors such as electrochemical reactors, catalytic reactors, photocatalytic reactors and immobilized enzyme biochemical reactors suitable for conducting diffusion controlled liquid – solid reactions was highlighted. Advantages of the present reactor in conducting small scale production compared to other reactors were pointed out.